Psychological Characteristics of PON South Sumatra Athletes in Terms of Team Sports - Khoirul Anwar Pulungan; Agus Kristiyanto; Sulaiman Sulaiman; Heny Setyawati (Universitas Negeri Semarang, 2021)
This study aims to reveal: (1) the psychological characteristics of PON South Sumatra athletes in terms of team sports, (2) differences the psychological characteristics between male and female athletes in terms of team sports. This research approach was quantitative using survey method with research design a restrospective causal- comparative design. All subjects in the population were included in the study with a total of 56 athletes. Data collection techniques using The Psychological Skills Inventory for Sports (PSIS) questionnaire. Data analysis techniques using independent sample t-test with significance level 0.05. The results of this study showed that: (2) the psychological characteristics of PON South Sumatra athletes were reviewed from team sports in the Medium category with an average score of 42.5, (2) There were significant differences between male athletes and female athletes with a mean score of 127.15 for male athletes and 121.45 for female athletes. So it can be concluded that the psychological characteristics of PON South Sumatra athletes in terms of team sports were moderate category, and there were significant differences between the psychological characteristics of male and female athletes.